Modelling the effects of salt solutions on the hydration of calcium ions - Di Tommaso, D.; Ruiz-Agudo, E.; de Leeuw, N.; Putnis, Andrew; Putnis, C. (R S C Publications, 2014)
Classical molecular dynamics simulations of several aqueous alkali halide salt solutions have been used to determine the effect of electrolytes on the structure of water and the hydration properties of calcium ions. Compared with the simulations of Ca2+ ions in pure liquid water, the frequency of water exchange in the first hydration shell of calcium, which is a fundamental process in controlling the reactivity of calcium(II) aqua-ions, is drastically reduced in the presence of other electrolytes in solution. The strong stabilization of the hydration shell of Ca2+ occurs not only when the halide anions are directly coordinated to calcium, but also when the alkali and halide ions are placed at or outside the second coordination shell of Ca2+, suggesting that the reactivity of the first solvation shell of the calcium ion can be influenced by the specific affinity of other ions in solution for the water molecules coordinated to Ca2+. Analysis of the hydrogen-bonded structure of water in the vicinity of the calcium ion shows that the average number of hydrogen bonds per water molecules, which is 1.8 in pure liquid water, decreases as the concentration of alkali–halide salts in solution increases, and that the temporal fluctuations of hydrogen bonds are significantly larger than those obtained for Ca2+ in pure liquid water. This effect has been explained in terms of the dynamics of reorganization of the O–H X (X = F, Cl and Br) hydrogen bond. This work shows the importance of solution composition in determining the hydrogen-bonding network and ligand-exchange dynamics around metal ions, both in solution and at the mineral–water interfaces, which in turn has implications for interactions occurring at the mineral–water interface, ultimately controlling the mobilization of ions in the environment as well as in industrial processes.